2010
DOI: 10.1088/1674-0068/23/06/701-706
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polyaniline/Silver Nanocomposite Under Gamma-ray Irradiation

Abstract: Polyaniline (PANI)/silver composite was one-step synthesized under γ-ray irradiation. The structure of the composite was characterized by Fourier transform infrared spectroscopy, UV-Visible, and X-ray diffraction, which indicated that PANI and face-centered-cubic silver were synthesized under γ-ray irradiation. The reaction mechanism were discussed, which revealed that the PANI was formed by the reaction of aniline cation radicals formed by the reaction of aniline cation and ·OH, and Ag was formed by the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…1B(c)), which confirms the formation core-shell nanocomposites. 15,16 FT-IR spectroscopy gives more insightful information for pure PANI and PANI-Ag core-shell nanorods (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…1B(c)), which confirms the formation core-shell nanocomposites. 15,16 FT-IR spectroscopy gives more insightful information for pure PANI and PANI-Ag core-shell nanorods (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Second, gold and silver NPs offer unique properties that can benefit tissue-engineering applications [101]. These NPs have been shown to enhance the mechanical properties of tissues, improve cell adhesion and proliferation, and promote tissue regeneration [102]. Furthermore, gold and silver NPs possess antimicrobial properties that can help prevent infections in tissue-engineered constructs.…”
Section: Polyaniline and Metal Compositionmentioning
confidence: 99%
“…111 Huang et al developed an one pot method for polyaniline/silver composites under γ-irradiation which revealed that the PANI nanofibers were formed by the reaction of aniline cation radicals formed by the reaction of the aniline cation and • OH, and the Ag NPs were formed by the reaction of Ag + and e − aq . 112 Recently Remita's group reported a series of radiolytic syntheses of PEDOT nanostructures and also studied the mechanism in detail. Lattach et al developed self-assembled hydrophilic PEDOT nanostructures via an oxidation process initiated by HO • radicals produced by water radiolysis without using chemical initiators.…”
Section: Template-free Synthesismentioning
confidence: 99%